Force of nature [videorecording (DVD)] - Hirsch, Emile, 1985-; Bosworth, Kate, 1983-; Gibson, Mel; Zayas, David; Cayo, Stephanie; Catlett, Will; Temmel, Swen, 1991-; Olson, Tyler Jon; Ramos, Jorge Luis (Lionsgate, 2020)
While trying to evacuate residents from an apartment complex during an intense hurricane, including a grizzled ex-cop and his daughter, a young police officer is thrust into further danger as a gang of thieves attempt to pull off a mysterious heist in the building.